Emerging issues in public health genomics - Roberts, J. Scott (Annu Rev Genomics Hum Genet, 2014)
This review highlights emerging areas of interest in public health genomics. First, recent advances in newborn screening (NBS) are described, with a focus on practice and policy implications of current and future efforts to expand NBS programs (e.g., via next-generation sequencing). Next, research findings from the rapidly progressing field of epigenetics and epigenomics are detailed, highlighting ways in which our emerging understanding in these areas could guide future intervention and research efforts in public health. We close by considering various ethical, legal and social issues posed by recent developments in public health genomics; these include policies to regulate access to personal genomic information; the need to enhance genetic literacy in both health professionals and the public; and challenges in ensuring that the benefits (and burdens) from genomic discoveries and applications are equitably distributed. Needs for future genomics research that integrates across basic and social sciences are also noted.